2007
DOI: 10.1111/j.1532-7078.2007.tb00235.x
|View full text |Cite
|
Sign up to set email alerts
|

The Other‐Race Effect in Infancy: Evidence Using a Morphing Technique

Abstract: Human adults are more accurate at discriminating faces from their own race than faces from another race. This other-race e$ecr (ORE) has been characterized as a reflection of face processing specialization arising from differential experience with own-race faces. We examined whether 3.5-month-old infants exhibit ORE using morphed faces on which adults had displayed a crossover ORE (i.e., Caucasians performed better on Caucasian faces and Asians performed better on Asian faces). In this experiment, Caucasian i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
76
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(84 citation statements)
references
References 33 publications
6
76
2
Order By: Relevance
“…Previous reports have shown that the ORE develops early in life in Caucasian infants (Hayden et al, 2007; Kelly et al, 2007b; Sangrigoli & de Schonen, 2004b). The purpose of this study was to investigate whether the developmental pattern reported by Kelly and colleagues (2007b) extends to an additional ethnic group, namely, Han Chinese.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Previous reports have shown that the ORE develops early in life in Caucasian infants (Hayden et al, 2007; Kelly et al, 2007b; Sangrigoli & de Schonen, 2004b). The purpose of this study was to investigate whether the developmental pattern reported by Kelly and colleagues (2007b) extends to an additional ethnic group, namely, Han Chinese.…”
Section: Discussionmentioning
confidence: 95%
“…Sangrigoli and de Schonen (2004b; see also Hayden, Bhatt, Joseph, & Tanaka, 2007) demonstrated that an ORE for “Asiatic” faces is present at 3 months of age in French Caucasian infants, but it is also easily removed with minimal exposure to Asiatic faces, suggesting that a robust ORE does not emerge until later in life. To investigate this issue more fully, Kelly and colleagues (2007b) adopted a similar but slightly modified paradigm as Sangrigoli and de Schonen (2004b) (see Kelly et al, 2007b, for a detailed description of the methodological differences) in which they extended the range of face stimuli to four distinct ethnic groups (African, Middle Eastern, Chinese, and Caucasian) and tested three different age groups of British Caucasian infants (3-, 6-, and 9-month-olds).…”
Section: Introductionmentioning
confidence: 99%
“…Further, infants are better at recognizing individual novel faces own-race compared to other-race faces, and show the ability to form perceptual categories based on race [113114]. As with visual preferences, these benefits are likely based on expertise for processing familiar faces: exposing infants to other-race faces in the laboratory can eliminate own-race facial recognition advantages [115116].…”
Section: Social Categorization In Childhoodmentioning
confidence: 99%
“…The same face pairs were used in the experimental and control conditions. Using Adobe Photoshop, the hair was removed from the head (this is a common practice in studies investigating the ORE [e.g., Hayden et al, 2007;Walker & Tanaka, 2003]). In addition, in order to avoid pop-out based on low-level features, we equated for skin tone within the pairs of faces.…”
Section: Stimulimentioning
confidence: 99%